Health benefits of algae and marine-derived bioactive metabolites for modulating ulcerative colitis symptoms - Najmeh Oliyaei; Saghar Zekri; Aida Iraji; Alireza Oliyaei; Romina Tanideh; Nadiar M. Mussin; Amin Tamadon; Nader Tanideh (Journal of Functional Foods)
Ulcerative colitis is a type of inflammatory bowel disease (IBD) that has risen around the world in recent years. Diet, lifestyle, genetics, stress, are the risk factors of ulcerative colitis. Indeed, oxidative stress, impairment of the intestinal barrier, inflammation, and dysbiosis of gut microbiota are the main pathways involved in ulcerative colitis. Therefore, using the anti-inflammatory and antioxidant ingredients can modulate the ulcerative colitis symptoms. Recent investigations in functional foods have demonstrated that diet and fortified foods play major therapeutic effects in human health, thus, the natural remedies have become an attractive approach. Among various natural substances, algae and marine products are valuable sources and rich in a wide range of metabolites with biological activities that can ameliorate ulcerative colitis signs. It has been reported that algal sulfated polysaccharides, peptides, pigments, polyphenols, and marine oil are useful for controlling ulcerative colitis via different pathways including modulating of TNF-α and other related inflammatory cytokines secretion, increasing the antioxidant enzymes [superoxide dismutase (SOD) and catalase(CAT)] activities, reduction of myeloperoxidase (MPO) activity and malondialdehyde (MDA) production, improving the intestinal barrier function and repairing histological damage in the colon. This review focused on the pathology of ulcerative colitis, pathogenesis and key inflammatory pathways, and the role of algae and marine-based metabolites for reduction of ulcerative colitis signs via alleviating the inflammation cytokines secretion, and improving the barrier function and gut microbiota.